Social Stratification Reflected In Fyodor Dostoyevsky's Crime And Punishment (1866): A Marxist Approach - Amalia, Anna Maoza; , Dr. M. Thoyibi, MS. (2017)
Anna Maoza Amalia/ A320130035 , SOCIAL STRATIFICATION REFLECTED IN FYODOR DOSTOYEVSKY'S CRIME AND PUNISHMENT (1866): MAR XIST APPROACH. School of Teacher Training and Education, Muhammadiyah University of Surakarta. April, 2017. This study aims to investigate social stratification in Crime and Punishment novel. The study describes the indicators of social stratification, sho ws how social stratification depicted in the novel, and reveals the reason of Dostoyevsky why he t akes social stratification in his novel. This research is qualitative. In analyzing this novel, the researcher uses Marxist approach. The primary data source is taken from Crime and Punishment novel by Fyodor Dostoyevsky. While the secondary data sources are other sources such as journals or articles related to the primary data. The result of the study shows the following conclusions. First, there are three ind icators of social stratification such as occupation, property, and authority. Second, social stratification depicted in this novel through characters, setting, events, and diction. Third, the reason why Fyodor Dostoyevsky raises social stratification in hi s novel is to criticize the reign at that era. He concerns with the poor people that oppressed. Keywords: Crime and Punishment, Marxist, Social Stratification